Transcirculation Approach for Mechanical Thrombectomy in Acute Ischemic Stroke: A Multicenter Study and Review of the Literature - Roa, Jorge A.; Maud, Alberto; Jabbour, Pascal; Dabus, Guilherme; Pazour, Avery; Dandapat, Sudeepta; Ortega-Gutierrez, Santiago; Paez-Granda, Diego; Kalousek, Vladimir; Hasan, David M.; Samaniego, Edgar A. (Frontiers in Neurology, 2020)
Background: Transcirculation approaches, which consist of primary catheterization of a target artery from the contralateral side or opposite cerebral circulation, provide alternate endovascular routes when anterograde interventions are not feasible. We aimed to assess the safety and efficacy of mechanical thrombectomy (MT) through a transcirculation route. Methods: Six centers provided retro¬spective data on acute ischemic stroke (AIS) patients who underwent MT via transcirculation approaches. Demographics and technical details of the endovascular intervention were collected. Recanalization rates, peri-procedural complications and clinical/angiographic outcomes immediately after the procedure and at last available follow-up were assessed. A review of the literature reporting on AIS patients whom underwent transcirculation MT was also performed. Results: Our multicenter study included 14 AIS patients treated through transcirculation routes. Mean age was 57.8 ± 11.9 years, and 10 (71.4%) were men. Mean NIHSS at admission was 18.4 (range 8-27). TICI 2b-3 recanalization was achieved in 10/14 (71.4%) patients. Three patients died after intervention: one due to late recanalization, one due to acute in-stent thrombosis, and one due to a procedure-related thromboembolic brainstem infarct. Of 11 surviving patients with follow-up available (mean 9.7 months), mRS 0-2 was achieved in 6 (54.5%) cases. Our review of the literature pooled a total of 37 transcirculation MT cases. Most common occlusions were tandem lesions (ICA + MCA = 64.9%) and BA + bilateral VA (18.9%). ACOM and PCOM were crossed in 18 (48.6%) cases each; one patient required a combined ACOM-PCOM approach. Primary recanalization technique included intra-arterial (IA) thrombolytics alone in 10 (27%), angioplasty ± stenting in 6 (16.2%), stent-retriever in 8 (21.6%), contact aspiration in 6, and combined (MT ± IA-thrombolytics) in 6 cases. Twenty-eight (75.7%) AIS patients achieved successful TIMI 2-3/TICI 2b-3 recanalization. After a mean follow-up of 6.7 months, 23/31 (74.2%) patients achieved a favorable functional outcome. Conclusions: Transcirculation approaches may be used to access the target lesion when the parent artery cannot be crossed through conventional antegrade routes. These techniques are feasible but should be reserved as a bailout maneuver when anterograde MT is not possible. Newer endovascular devices have improved neurological and angiographic outcomes in transcirculation cases.